Does This Patient Need Blood Cultures? A Scoping Review of Indications for Blood Cultures in Adult Nonneutropenic Inpatients. (14th January 2020) - Fabre, Valeria; Sharara, Sima L; Salinas, Alejandra B; Carroll, Karen C; Desai, Sanjay; Cosgrove, Sara E
Abstract: Guidance regarding indications for initial or follow-up blood cultures is limited. We conducted a scoping review of articles published between January 2004 and June 2019 that reported the yield of blood cultures and/or their impact in the clinical management of fever and common infectious syndromes in nonneutropenic adult inpatients. A total of 2893 articles were screened; 50 were included. Based on the reported incidence of bacteremia, syndromes were categorized into low, moderate, and high pretest probability of bacteremia. Routine blood cultures are recommended in syndromes with a high likelihood of bacteremia (eg, endovascular infections) and those with moderate likelihood when cultures from the primary source of infection are unavailable or when prompt initiation of antibiotics is needed prior to obtaining primary source cultures. In syndromes where blood cultures are low-yield, blood cultures can be considered for patients at risk of adverse events if a bacteremia is missed (eg, patient with pacemaker and severe purulent cellulitis). If a patient has adequate source control and risk factors or concern for endovascular infection are not present, most streptococci or Enterobacterales bacteremias do not require routine follow-up blood cultures. Abstract : Published recommendations for indications for blood cultures are limited. We conducted a scoping review of the evidence and found that blood cultures are high-yield in only a limited set of syndromes/clinical scenarios.